Answer:
C. Exponential decay
Step-by-step explanation:
Answer:
Step-by-step explanation:
Radius =6 ft
Area of circle = πr²
= 3.14 * 6 * 6
= 113.04 ft²
base = 10.39 ft
height = 6+3 = 9 ft
![Area \ of \ triangle = \dfrac{1}{2}*base * height\\\\\\=\dfrac{1}{2}*10.39*9\\](https://tex.z-dn.net/?f=Area%20%5C%20of%20%5C%20triangle%20%3D%20%5Cdfrac%7B1%7D%7B2%7D%2Abase%20%2A%20height%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B1%7D%7B2%7D%2A10.39%2A9%5C%5C)
= 46.76 ft²
Area of the shaded region = area of circle - area of triangle
= 113.04 - 46.76
= 66.28
= 66.3 ft²
Answer:
في الأسبوع الماضي ، اشترى تشين جالونًا من البنزين للغالون الواحد. هذا الأسبوع اشترى جالونًا من البنزين مقابل الدولار للغالونفي الأسبوع الماضي ، اشترى تشين جالونًا من البنزين للغالون الواحد. هذا الأسبوع اشترى جالونًا من البنزين مقابل الدولار للغالونفي الأسبوع الماضي ، اشترى تشين جالونًا من البنزين للغالون الواحد. هذا الأسبوع اشترى جالونًا من البنزين مقابل الدولار للغالون
Step-by-step explanation:
في الأسبوع الماضي ، اشترى تشين جالونًا من البنزين للغالون الواحد. هذا الأسبوع اشترى جالونًا من البنزين مقابل الدولار للغالونفي الأسبوع الماضي ، اشترى تشين جالونًا من البنزين للغالون الواحد. هذا الأسبوع اشترى جالونًا من البنزين مقابل الدولار للغالونفي الأسبوع الماضي ، اشترى تشين جالونًا من البنزين للغالون الواحد. هذا الأسبوع اشترى جالونًا من البنزين مقابل الدولار للغالونفي الأسبوع الماضي ، اشترى تشين جالونًا من البنزين للغالون الواحد. هذا الأسبوع اشترى جالونًا من البنزين مقابل الدولار للغالونفي الأسبوع الماضي ، اشترى تشين جالونًا من البنزين للغالون الواحد. هذا الأسبوع اشترى جالونًا من البنزين مقابل
275,000 km
The moons A, B, C form a right triangle with AC forming a hypotenuse with the diameter of the planet and the distance of both moons from the surface. So add A to the surface, plus the diameter of the planet, plus surface to c.
115000+45000+115000 = 275000
Answer:
The correct option is B) ![f(x) =(x^2+1)(x^2+4x+5)](https://tex.z-dn.net/?f=f%28x%29%20%3D%28x%5E2%2B1%29%28x%5E2%2B4x%2B5%29)
Step-by-step explanation:
Consider the provided function.
and ![d(x) = x^2+1](https://tex.z-dn.net/?f=d%28x%29%20%3D%20x%5E2%2B1)
We need to divide f(x) by d(x)
As we know: Dividend = Divisor × Quotient + Remainder
In the above function f(x) is dividend and divisor is d(x)
Divide the leading term of the dividend by the leading term of the divisor:![\frac{x^4}{x^2}=x^2](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E4%7D%7Bx%5E2%7D%3Dx%5E2)
Write the calculated result in upper part of the table.
Multiply it by the divisor: ![x^2(x^2+1)=x^4+x^2](https://tex.z-dn.net/?f=x%5E2%28x%5E2%2B1%29%3Dx%5E4%2Bx%5E2)
Now Subtract the dividend from the obtained result:
![(x^4 + 4x^3 + 6x^2 + 4x + 5)-(x^4-x^2)=4x^3+5x^2+4x+5](https://tex.z-dn.net/?f=%28x%5E4%20%2B%204x%5E3%20%2B%206x%5E2%20%2B%204x%20%2B%205%29-%28x%5E4-x%5E2%29%3D4x%5E3%2B5x%5E2%2B4x%2B5)
Again divide the leading term of the obtained remainder by the leading term of the divisor: ![\frac{4x^3}{x^2}=4x](https://tex.z-dn.net/?f=%5Cfrac%7B4x%5E3%7D%7Bx%5E2%7D%3D4x)
Write the calculated result in upper part of the table.
Multiply it by the divisor: ![4x(x^2+1)=4x^3+4x](https://tex.z-dn.net/?f=4x%28x%5E2%2B1%29%3D4x%5E3%2B4x)
Subtract the dividend:
![(4x^3+5x^2+4x+5)-(4x^3+4x)=5x^2+5](https://tex.z-dn.net/?f=%284x%5E3%2B5x%5E2%2B4x%2B5%29-%284x%5E3%2B4x%29%3D5x%5E2%2B5)
Divide the leading term of the obtained remainder by the leading term of the divisor: ![\frac{5x^2}{x^2}=5](https://tex.z-dn.net/?f=%5Cfrac%7B5x%5E2%7D%7Bx%5E2%7D%3D5)
Multiply it by the divisor: ![5(x^2+1)=5x^2+5](https://tex.z-dn.net/?f=5%28x%5E2%2B1%29%3D5x%5E2%2B5)
Subtract the dividend:
![(5x^2+5)-(5x^2+5)=0](https://tex.z-dn.net/?f=%285x%5E2%2B5%29-%285x%5E2%2B5%29%3D0)
Therefore,
Dividend = ![x^4 + 4x^3 + 6x^2 + 4x + 5](https://tex.z-dn.net/?f=x%5E4%20%2B%204x%5E3%20%2B%206x%5E2%20%2B%204x%20%2B%205)
Divisor = ![x^2+1](https://tex.z-dn.net/?f=x%5E2%2B1)
Quotient = ![x^2+4x+5](https://tex.z-dn.net/?f=x%5E2%2B4x%2B5)
Remainder = 0
Dividend = Divisor × Quotient + Remainder
![f(x) = (x^2+1)(x^2+4x+5)](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x%5E2%2B1%29%28x%5E2%2B4x%2B5%29)
Hence, the correct option is B) ![f(x) =(x^2+1)(x^2+4x+5)](https://tex.z-dn.net/?f=f%28x%29%20%3D%28x%5E2%2B1%29%28x%5E2%2B4x%2B5%29)